Pengaruh LDR, BI Rate, CAR, NPL Terhadap Penyaluran Kredit UMKM di Bank Umum Provinsi Bali Periode 2004.I-2013.IV - Putra, I.G.A.N. Bagus Grahadika; Wirathi, I.G. A.P. (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 12, Desember 2014 (pp. 549-623), 2014)
The purpose of this study was to determine the effect of LDR, the BI Rate, CAR, NPL against SME lending in commercial banks Bali Province first quarter period of 2004 - 2013 fourth quarter. This study used a quantitative research. The study sample was drawn from the monthly financial statements of Bank Indonesia for 10 periods, the first quarter period of 2004 - 2013 fourth quarter. The data analysis technique used in this study is multiple linear regression. It was found that the value of LDR (LDR) of commercial banks in Bali Province fluctuated ranging from 50.13 percent to 76.67 percent. Furthermore, LDR, the BI rate, CAR, and a significant effect simultaneously NPL to total loans disbursed SME banks in Bali Province. Finally, LDR positive and significant effect, the BI rate and a significant negative effect, no effect of CAR and non-performing loans and a significant negative effect on the amount of SME loans disbursed commercial banks in Bali Province.
Keywords: LDR, BI Rate, CAR, NPL, Penyaluran Kredit